Management Career Path for Construction Engineers and the Transition Stage - Abu Hmaid, Hala (2015)
Based on several recent studies it had been observed that a lot of engineers are interested to follow a managerial path in their career life. This research is aiming to study the management career path for engineers in the construction industry, focusing on the transition stage to provide guidance for the engineers to override this stage successfully. Wherein, researchers found that engineers face challenges in their transition process from technical engineering to a management position. This goal has been achieved through an extensive literature review that was conducted to provide an in-depth exploration for the objectives of the study, which lead to the conceptual framework of the study that present the factors that contributes in the transition process for engineers, these factors are: personal characteristics, management skills and working experience. These principles was examine through a qualitative approach to present different experiences for engineers who pursue a managerial path successfully, that was approach through a case study method using a semi-structural interviews; interviews was conducted with two engineers who had a successful experience in the transition from technical engineering to a management position and were successful in fulfilling an important managerial position. The cases were analyzed and compared with the literature review findings. The most important findings of the research recommend that construction organizations can’t promote engineers for a managerial position based on their technical competencies only, they need to take in account other principles like personal characteristics, and managerial skills, in addition construction organizations must provide adequate training for engineers before promoting them officially to a management position. Universities need to add a management course to the curriculums of engineering degrees, and it was highly recommended for engineers to benefit from others’ experience and challenges in the transition to help them build an insight for the challenges that they might face.